Phylogenetic Inference Using Cytochrome C Oxidase Subunit I (COI) in the Poultry Red Mite, Dermanyssus gallinae in the United Kingdom Relative to a European Framework - Karp-Tatham, Eleanor; Küster, Tatiana; Angelou, Athanasios; Papadopoulos, Elias; Nisbet, Alasdair J.; Xia, Dong; Tomley, Fiona M.; Blake, Damer P. (Frontiers in Veterinary Science, 2020)
The poultry red mite (Dermanyssus gallinae), an obligatory blood feeding ectoparasite, is primarily associated with laying hens where it is estimated to cause losses of ~€231 million per annum to European farmers. Moderate to high infestation levels result in negative impacts on hen welfare, including increased cannibalism, irritation, feather pecking, restlessness, anaemia and mortality. Acaricides are currently the prevailing method of population control for D. gallinae, although resistance against some classes of acaricide has been widely reported. The development of resistance highlights a growing need for research into alternative control methods, including the development of a suitable and effective vaccine. Understanding the genetic structure of D. gallinae populations can support improved management of acaricide resistance and sustainability of future vaccines, but limited data are currently available. The aim of this study was to characterise D. gallinae isolates from Europe, targeting the cytochrome c oxidase subunit 1 (COI) gene to gain an insight into population structure and genetic diversity of currently circulating mites. Dermanyssus gallinae isolates were collected from Albania, Belgium, Croatia, Czech Republic, Denmark, France, Greece, Italy, the Netherlands, Portugal, Romania, Slovenia, Turkey and the United Kingdom. Genomic DNA was extracted from individual adult D. gallinae mites and a 681bp fragment of the COI gene was amplified and sequenced. Phylogenetic analyses of 195 COI sequences confirmed the presence of multiple lineages across Europe with 76 distinct haplotypes split across three main haplogroups, including six sub-haplogroups. Importantly, there is considerable inter- and intra-country variation across Europe that could be a consequence of movement of poultry, transfer of contaminated equipment and/or materials and husbandry practices.